2018
DOI: 10.1002/jca.21671
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange for heparin‐induced thrombocytopenia in patients on extracorporeal circuits: A challenging case and a survey of the field

Abstract: Current management of heparin‐induced thrombocytopenia (HIT) involves prompt discontinuation of all heparin products and concomitant initiation of a direct thrombin or anti‐Xa inhibitor for anticoagulation. In the setting of HIT complicated by an urgent need for cardiopulmonary bypass (CPB), the safety and the efficacy of short‐term heparin‐based anticoagulation after therapeutic plasma exchange (TPE) have been previously demonstrated. Patients with HIT requiring TPE are frequently on extracorporeal circuits (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…In this category, there are 14 studies with 30 cases. 5,[60][61][62][63][64][65][66][67][68] Case-level data are summarized in Table 3.…”
Section: Treatment Indication 3: Cardiopulmonary Bypass Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…In this category, there are 14 studies with 30 cases. 5,[60][61][62][63][64][65][66][67][68] Case-level data are summarized in Table 3.…”
Section: Treatment Indication 3: Cardiopulmonary Bypass Surgerymentioning
confidence: 99%
“…In 29 cases, the average number of TPE was three (range 1-8). 5,31,[61][62][63][64][65][66][67][68][69][70][71] One patient reported as undergoing two TPEs underwent two CPB procedures and received one TPE prior to each CPB case. In 24 cases reporting the treatment schedule, cases were treated once (n = 14), daily (n = 5), every other day (n = 3), and daily/every other day (n = 2).…”
Section: Tpe Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma exchange may be performed in patients undergoing ECMO who have heparin-induced HIT or significant thrombosis and require the rapid elimination of excessive anti-PF4-heparin antibodies [187,188]. Several studies have shown that plasma exchange is effective for HIT [189].…”
Section: Plasma Exchange Recommendation 25: Plasma Exchange Eliminatementioning
confidence: 99%
“…These large intravascular anti‐heparin/PF4 antibody complexes can be removed using therapeutic plasma exchange (TPE). In fact, TPE has been demonstrated, in case reports and case series, to be effective in decreasing anti‐heparin/PF4 antibodies, treating acute HIT complications, and facilitating heparin re‐exposure in patients with acute or subacute HIT …”
Section: Introductionmentioning
confidence: 99%